Role of radiological methods of diagnostics at simultaneous pancreas-kidney transplantation - A. V. Pinchuk; I. V. Dmitriev; I. E. Selina; R. Sh. Muslimov; Ye. A. Lapshina; M. V. Parkhomenko; A. S. Kondrashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2015)
Aim of investigation. To characterize radiological methods of diagnostics of surgical complications after simultateous pankreas-kidney transplantation (SPKT).Material and methods. From January, 2008 to June, 2014 overall 40 patients with the type 1 diabetes mellitus complicated by terminal diabetic nephropathy, underwent SPKT, including 17 cases (42,5%) — of intraperitoneal transplantation and 23 (57,5%) — of retroperitoneal transplantation. Mean age of patients was 35,7±6,36 year. Of all recipients 19 were women (47,5%) and 21 — men (52,5%). Results. Of 15 patients after SPKT 21 surgical complications were diagnosed, overwhelming majority of them have been corrected successfully. Only in one case the pancreatic transplant was lost due to postoperative surgical complications.Conclusions. Duly diagnostics and the proven choice of miniinvasive techniques for treatment of surgical complications became possible due to wide and urgent application of the whole spectrum of available radiological methods.